How Inflation is a Policy Nowadays - Lucian Croitoru (Transylvanian Review of Administrative Sciences, 2023)
After World War II, democracies witnessed transformations that were and are much more lenient vis-à-vis the rise in inflation. The main institutional changes that have occurred gradually ever since and can combine nowadays to fuel inflation refer to (i) the shift in ideas referring to equality and redistribution, (ii) the labor market policies, (iii) bringing man’s natural environment to the level of importance of the social environment, with a particular focus on climate, and (iv) preserving a large capacity of the government to produce inflation in a context in which political power has granted independence to the central bank in terms of monetary policy. We show how features of society listed under items (i)- (iv) had combined to lead to low and stable inflation during 1982-2008, to lower than desired inflation during 2009-2020, and to the high inflation starting with 2021. The inflation-taming efforts succeeded only when three elements acted jointly: (A) raising the interest rate while no longer considering the inflation-unemployment tradeoff, impacting features (ii) and (iv); (B) adjusting budget deficits and stabilizing fiscal expectations, impacting feature (iv); (C) measures for reviving economic freedom, with an impact on features (i), (ii), and (iii).